Quality Control Intelligent Manufacturing, Robust Design and Charts - Li, Pengzhong; António Rodrigues Pereira, Paulo; Navas, Helena (IntechOpen, 2021)
Quality control is changing along with the manufacturing environment. A series of revolutionary changes will occur in management contents, methods, capabilities, and real-time effectiveness and efficiency of management. As an essential factor in intelligent manufacturing, quality control systems require real and comprehensive innovation. Focused on new trends and developments in quality control from a worldwide perspective, this book presents the latest information on novel approaches in quality control. Its thirteen chapters cover three topics: intelligent manufacturing, robust design, and control charts.